Cassava research and development in eastern and southern Africa - Porto, M.; Asiedu, Robert (1993)
Cassava is the major root crop in eastern and southern Africa. It is an important source of calories for the inhabitants of such countries as Uganda, Malawi, and Mozambique. It may also be the best alternative for overcoming the food scarcities caused by frequent droughts in the region.